Police Legal Responsibilityy For Crime and Thieft Involving Violence - Jumadi, Jumadi; Ardha, Dea Justicia; Jafar, Abdul; Saputra, Muhammad Adi (Nurani, 2023)
The Indonesian National Police obtains a mandate from laws tasked with maintaining security and order, protecting, serving, enforcing the law and protecting the public. One of these tasks is the prevention of theft with violence crimes by the Police Resort in the East OKU. In seeking answers to this problem, the author used empirical research methods, by conducting interviews with several parties, including the East OKU Police Resort and the perpetrators of violent crimes. The results of the study suggest that, first, the things that cause theft with violence crimes are caused by two factors, namely endogenous and exogenous factors, but the causative factors that often cause theft with violence crimes in the East OKU such as economic level, low education that causes unemployment, the environment, and lack of legal awareness, and supported by situations and conditions. The second is done by using penal and non-penal effort. Prevention with Penal efforts focuses more on the repressive nature, that is, actions carried out after the occurrence of crime. The study's findings revealed the effectiveness of criminal law and policy in preventing violent stealing.